Low frequency of asymptomatic dengue virus-infected donors in blood donor centers during the largest dengue outbreak in Taiwan - Tsai, Jih-Jin; Lin, Ping-Chang; Tsai, Ching-Yi; Wang, Ying-Hui; Liu, Li-Teh (PLOS ONE, 2018)
To determine the prevalence of asymptomatic dengue virus-infected blood donors during the largest dengue outbreak in Taiwan history occurred in 2015, we examined the evidence of dengue virus (DENV) infection by the detection of DENV RNA genome using real-time reverse transcription-polymerase chain reaction (real-time RT-PCR), DENV NS1 antigen using rapid diagnosis test (RDT) and anti-dengue antibody using IgM/IgG capture enzyme-linked immunosorbent assay (capture ELISA) and RDT in eight thousand serum samples from blood donations to the blood centers of the Taiwan Blood Services Foundation (TBSF) in Kaohsiung City and Tainan City during the largest dengue outbreak in Taiwan history occurred in 2015. Only one serum sample was positive for DENV RNA detection by using dengue-specific real-time RT-PCR, the virus was DENV-2 determined by serotype-specific real-time RT-PCR and sequencing, and the DENVs in the serum were confirmed as being infectious by a plaque assay. The recipient of this blood did not develop any dengue fever symptom on follow-up. None of the samples was NS1 RDT-reactive. Seventeen IgM-positive samples were identified. There was a low prevalence of asymptomatic confirmed or probable DENV-infected blood donors in our study (0.013% and 0.21%, respectively), and no symptomatic transfusion-transmitted dengue (TT dengue) was developed during the largest dengue outbreak in Taiwan history in highly endemic areas and periods.